Interaction of bottom-up and top-down processes in the perception of ambiguous figures - Intaitė, Monika (2013)
Ambiguous figures reverse their appearance during prolonged viewing and can be perceived in two (or more) available interpretations. Both physical stimulus manipulations and cognitive control influence the perception of ambiguous figures, but the underlying mechanisms remain poorly understood. In the current study, the perception of an ambiguous figure was manipulated by adaptation to unambiguous figures and/or placing the ambiguous figure into a context of unambiguous figures. Our results indicate that both adaptation and context can effectively modulate perception of the ambiguous figure. When manipulated together, adaptation and context processes showed additive effects upon the perception of the ambiguous figure implying the independent mechanisms. Thus, top-down and bottom-up processes seem to influence the perception of the ambiguous figures independently and neither seems to be uniquely responsible for the generation of perceptual changes.